UPAYA MENINGKATKAN PEMBELAJARAN LEMPAR CAKRAM GAYA MEMUTAR DENGAN MEDIA BAN PADA SISWA KELAS IX C SMP NEGERI 1 JUJUHAN - Asril Asril (Jurnal Muara Olahraga, 2021)
ABSTRACT: Discus throwing skills of students from how to hold a discus, the initial technique of throwing discs, discus throwing techniques, and body posture after throwing discs are still not good. This study aims to describe the learning process of rotating disc throwing with tire media in class IX C students at SMP Negeri 1 Jujuhan. This research is a Classroom Action Research. The subjects in this study were students of class IX C at SMP Negeri 1 Jujuhan, totaling 30 students. The instrument used is a discus throwing performance test. The data analysis technique used in this research is descriptive and quantitative in the form of percentages. Based on the results of the study, it can be concluded that the increase in discus throwing results through the media of used motorcycle tires is marked by an increase in the average score of students. The average value of students in the initial conditions is 67 with a percentage of completeness of 23.33%. This condition experienced an increase in the average score of students in the first cycle, which was 68.61 and the percentage of completeness was 60%. However, this increase has not yet reached the previously set target. Then after continuing to cycle II, the average value of students' discus throwing abilities again increased by 79.72 with a percentage of completeness of 93.33%. This shows that the predetermined target has been achieved so that the research is stopped in cycle II. The discus throwing learning process through used motorcycle tires was dynamic and fun, and the students' character of responsibility, confidence, competitiveness, and enthusiasm also increased in every meeting. Students actively carry out tasks and observe the movement of discus throwing techniques and discuss each other with friends, students' discus throwing abilities increase marked by students completing the KKM (Minimum Completeness Criteria) which is 75. Keywords: discus throwing, twisting style, tire media